Pengaruh Kualitas Produk, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Jasa Pengiriman Sicepat Ekspres Cabang Kecamatan Nganjuk - Luthfi Wahyu Priambudi; Moh. Saleh Udin; Heru Sutapa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of the variables product quality (X1), price (X2) and service quality (X3) on customer satisfaction (Y) at the Sicepat Express Delivery Service, Nganjuk District Branch. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the accidental sampling method, the number of samples in the research was 175 respondents at the Sicepat Express Delivery Service, Nganjuk District Branch. This research data was obtained through questionnaires, interviews and literature studies. The data analysis technique was carried out by describing the research data and analysis used, namely Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the research obtained the multiple linear regression equation Y = 3.185 + 0.278 0.000 < 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that product quality (X1), price (X2) and service quality (X3) simultaneously and significantly influence customer satisfaction.